"One stone two birds" or "you can't have your cake and eat it too"? Effects of device dimensions and position of the thermoelectric module on simultaneous solar-driven water evaporation and thermoelectric generation. Issue 1 (12th December 2022) - Wang, Haiwen; Shi, Yanying; Liu, Tiefeng; Zheng, Xiuwen; Gao, Shanmin; Lu, Jun
Abstract : Flexible CMF/Cu@CuS was fabricated as a photothermal conversion material (PCM) for simultaneous water evaporation and thermoelectric generation. By adjusting the position of the TE module in the PCM, a "one stone two birds" function can be realized. Abstract : Widespread interest has emerged in addressing the energy crisis that makes use of abundant solar energy to simultaneously evaporate water and produce electricity. Photothermal conversion materials (PCMs) and device structures are the two key platforms of photothermal conversion in the process of water evaporation (WE) and thermoelectric (TE) generation, and thus it is very important to reasonably design the structure of PCMs and the corresponding devices. Herein, three-dimensional (3D) and two-dimensional (2D) flexible carbon melamine foam (CMF) combined with Cu particles with excellent plasma effect and CuS with excellent UV-vis light absorption performance were assembled as a PCM (CMF/Cu@CuS). This functionalized porous CMF/Cu@CuS foam can not only realize WE but also simultaneously generate TE via the Seebeck effect. We found that the 3D structure favors WE and the 2D structure favors TE generation. Additionally, the TE generation is significantly impacted by the position of the TE module. Specifically, when the TE module is placed at the bottom of the PCM, the photothermal conversion efficiency (PCE) of the 3D structure reaches 86.8%, while that of the 2D structure is only 68.3% under 1.0 kW m −2 light irradiation. However, the maximum output TE power of the 2D structure reaches 69.3 μW cm −2, which is significantly higher than that by the 3D structure (2.4 μW cm −2 ). This difference in performance is due to the different thermal management abilities of the devices. The 3D structure can absorb extra heat from the surrounding environment, which is conducive to WE. However, the 3D structure leads to a small temperature difference between the hot and cold sides of the TE module, which is not conducive to TE generation. The 2D structure cannot absorb extra heat from the environment, which is not conducive to WE, but it causes a higher temperature difference between the hot and cold sides of the TE module, and is thus conducive to TE generation. A high WE rate can be attained as well as high TE power produced when the TE module is positioned close to the top surface of the PCM. According to this study, a properly adjusted TE module position is necessary to simultaneously achieve a high WE rate and output TE power.